Adaptation across multiple landscapes: Relatedness, complexity, and the long run effects of coordination in diversified firms - Chen, Mo; Kaul, Aseem; Wu, Brian (Strategic Management Journal, 2019)
Abstract Research Summary We study the effect of coordination between businesses on the adaptation of diversified firms. Using a simulation‐based approach, we show that coordination between businesses limits adaptation, causing the relative performance of diversified firms to decline relative to their focused counterparts over time, with this effect being strongest for moderate levels of relatedness between, and complexity within, businesses. Given complexity, firms diversifying into moderately related businesses may therefore be better off limiting coordination between businesses to a few key activities—if they diversify at all—sacrificing short run synergies for long run flexibility. Our study thus offers a novel argument for conglomerate diversification, while linking work on the costs of coordination in diversified firms to the literature on organizational adaptation. Managerial Summary While coordination of activities between businesses enables a diversified firm to realize synergies, it may also limit the flexibility of each business to adapt to changing conditions over time. Thus, the very cross‐business coordination that gives a diversified firm an advantage relative to its single business competitors in the short run may cause it to fall behind them in the long run. Using a mathematical simulation, we show that this negative effect is strongest for firms coordinating across moderately related businesses with activities that are highly interdependent. Multibusiness firms—especially moderately related diversifiers in complex businesses—may thus be better off coordinating only those activities that yield the greatest synergies, foregoing more marginal synergies in the short run for the sake of long run flexibility.